HUBUNGAN INTENSITAS PENCAHAYAAN RUANGAN DAN LAMA PENGGUNAAN GADGET DENGAN KELELAHAN MATA (ASTHENOPIA) PADA MAHASISWA YANG MELAKUKAN PENDIDIKAN JARAK JAUH - Deby Christine Sianturi; Wasisto Utomo; Sri Wahyuni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
During the Covid-19 pandemic, the use of gadgets is increasing because the learning process is carried out online, so there is a possibility of an increase in eye fatigue. The purpose of this study determine the relationship between the intensity of room lighting and the duration ofuse gadget with eye fatigue in students doing distance education. Methods of this study used a descriptive correlation design with aapproach cross sectional. The research sample was 82 students of the Faculty of Nursing who were taken based on inclusion criteria using simple random sampling technique. The analysis used is bivariate analysis usingtest chisquare. Results of this study there were 41 people (63.1%) who had room lighting intensity that was not up to standard and experienced severe eye fatigue. The statistical test results obtained for the relationship between room lighting intensity and eye fatigue (asthenopia) are p-value = 0.357, which is greater than = 0.05 (0.357 > 0.05). There are 34 people (61.8%) long using gadgets and experience severe eye fatigue. Statistical test results obtained for the relationship between long use of gadgets and eye fatigue (asthenopia), namely p-value = 0.761, greater than = 0.05 (0.761 > 0.05). The research instrument used is a questionnaire with valid test result of 0,463 – 0,689 > 0,444 and reliability test Cronbach Alpha’s with results of 0,701 > 0,6. The Conclusion of this study is Room Lighting Intensity and Long Use of Gadgets have no significant relationship with eye fatigue (asthenopia). Keywords : Duration, eye fatigue gadget, lighting intensity